(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the self-esteem of women undergoing mastectomies after breast cancer. Methodology: Observational, descriptive, analytical, cross-sectional and quantitative study. The research was carried out using electronic forms posted on applications through social networks. To collect data, an instrument for the sociodemographic and clinical profile of women was used, the Rosenberg Scale to assess self-esteem. Results: The study sample consisted of 55 women aged between 21 and 59 years, 52.7% were married or in a stable relationship, 45.5% completed higher education, 56.4% practiced physical activities and of these, 85 .5% have children, 21.8% are ex-smokers, 76.4% underwent surgery no more than 5 years ago and 70.9% of women used complementary treatment. And finally, we highlight that 36.4% of women underwent physical therapy after surgery. The majority of women assessed had a positive perception regarding all items on the self-esteem scale. Conclusion: After breast cancer, women who underwent mastectomy expressed a moderate to high level of self-esteem. It is extremely important for women to have high AE so that they can be more positive and more confident.